Ictiofauna de la zona intermareal rocosa del Área de Conservación Guanacaste, Pacífico Norte de Costa Rica: diversidad y aspectos ecológicos y biogeográficos - Angulo Sibaja, Arturo (2021)
Introduction: The rocky intertidal constitutes a dominant coastal seascape in the Eastern Tropical Pacific, harboring highly diverse and functionally complex biological communities. The knowledge about the diversity and the diverse biological processes that occur in such environments is, however, quite limited on a regional scale. Objective: Quantify, describe and compare (on a regional scale) the ichthyological diversity associated with the rocky intertidal zone of the Guanacaste Conservation Area (ACG), Costa Rica, as well as to evaluate and discuss some biogeographic and ecological patterns. Methods: A total of 49 tide pools were sampled between 2014 and 2019, at seven locations within the ACG. Data on absolute diversity (presence/absence of species) were obtained, in addition to some ecological data (residence status, development stage (s), trophic guild, aggregation and cryptic habits and generalized geographic distribution), these data were compared with published records from other surveys/inventories carried out at various locations (20) along the Eastern Pacific coast. Through a similarity analysis, both possible clustering patterns between localities (according to their species composition) and previous hypotheses of regionalization, under a biogeographic perspective, were evaluated. Results: A total of 67 species of bony fish were recorded in the rocky intertidal area of the ACG, being this the most diverse locality (with published data) in the Eastern Pacific. The components/categories “transitory” with 30 species (44.8 %), “juveniles” with 38 species (55.9 %), “carnivores” with 47 species (70.1 %), “solitary” with 32 species (47.8 %) and “endemic to the ETP” with 66 species (98 %), were dominant (in terms of the total number of species) within the ACG. The results of the similarity analysis supported the biogeographic division scheme, defined a priori; with the localities within the Californian, Cortez, Mexican, Panamic and Peruvian-Chilean provinces recovered as highly consistent groups. This structure is consistent with the effect of barriers such as the sandy gaps of Sinaloa and Central America, among others, limiting the flow of species between biogeographic units. Conclusions: The ACG has a high ichthyological diversity associated with its rocky intertidal zone, which is product of a unique combination of factors at the regional level. The results of this study reinforce the need to carry out more basic and applied studies with the aim of helping to better understand and know different key aspects of the dynamics and physical-chemical-biological processes occurring in intertidal zones, of its associated biological diversity, of its importance within the marine-coastal landscape as a continuum and of the possible effects that these environments could suffer due to the impact of human activities.